2008
DOI: 10.1016/j.jtcvs.2007.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac stem cells in the real world

Abstract: These data raise a cautionary note on the therapeutic exploitation of cardiac stem cells in patients with ischemic cardiomyopathy, who may be the elective candidates for regenerative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 20 publications
0
79
0
2
Order By: Relevance
“…Sheep CPC that are c-kit+Isl1+ and c-kit-isl1+ are present and clonable in normal sheep. Interestingly, sheep CPC can co-express c-kit and Isl1 whereas, a CPC population expressing c-kit and Isl1 has not been identified in humans [24,29]. As some c-kit+ cells also may be mast cells [29], the frequent co-expression of Isl1 and c-kit in our study indicates that c-kit positive cells in the sheep heart are cardiovascular progenitors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Sheep CPC that are c-kit+Isl1+ and c-kit-isl1+ are present and clonable in normal sheep. Interestingly, sheep CPC can co-express c-kit and Isl1 whereas, a CPC population expressing c-kit and Isl1 has not been identified in humans [24,29]. As some c-kit+ cells also may be mast cells [29], the frequent co-expression of Isl1 and c-kit in our study indicates that c-kit positive cells in the sheep heart are cardiovascular progenitors.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, sheep CPC can co-express c-kit and Isl1 whereas, a CPC population expressing c-kit and Isl1 has not been identified in humans [24,29]. As some c-kit+ cells also may be mast cells [29], the frequent co-expression of Isl1 and c-kit in our study indicates that c-kit positive cells in the sheep heart are cardiovascular progenitors. Pouly et al identified c-kit+CD45+ cells from human endomyocardial biopsies that do not express the stem cell markers MDR-1, Isl1 or CD105 [29], whereas, Koninckx et al identified c-kit+CD105+ cells that were CD45 negative [30].…”
Section: Discussionmentioning
confidence: 54%
“…Some reports have suggested that the main source of CSCs is the atrium, 13) especially the RA appendage; 9,12) however, another study demonstrated the opposite result. 25) When we compared the samples derived from the same patient, we observed that the number of c-kit pos cells was significantly higher in the RA than in LA. In addition, the number of cells from the ventricular tissue was the lowest.…”
Section: Discussionmentioning
confidence: 94%
“…In other words, an apparently fixed population of CPC resides in the heart postnatally. Pouly (Pouly et al, 2008) reported that CPC concentration in the right atrium is greater than that of the septum of transplanted hearts. Other myocardial niches have been reported.…”
Section: Postnatal Distribution Of Cpc In the Heartmentioning
confidence: 99%